The Role of food downstreaming in community welfare: Strawberry pancake in Berastagi from a Mashlahah perspective - Simarmata, Eprimanta; Atika, Atika; Syahbudi, Muhammad (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2025)
This research examines food downstreaming in Tanah Karo, with a focus on the production and development of strawberry pancakes in Berastagi, Indonesia, through a mashlahah (benefit) review. This study employs a qualitative approach, gathering primary data through observations and interviews with strawberry pancake businesses, as well as secondary data from a literature review. This study identifies the forms, challenges, and opportunities of food downstreaming in Tanah Karo, highlighting the potential of local commodities such as strawberries to increase economic value and community welfare. A mashlahah perspective was employed to assess the economic, social, and environmental benefits of strawberry pancake production, including job creation, income generation, waste reduction, and support for sustainable agriculture. The study concludes that food downstreaming, exemplified by the strawberry pancake industry, plays a strategic role in increasing the value of agricultural products and driving regional economic growth in Tanah Karo, and emphasizes the need for government support to overcome existing barriers and maximize its potential benefits. Public interest statements This research highlights the importance of food downstreaming in Tanah Karo, particularly in the processing of strawberries into pancakes. This approach enhances the value of agricultural products, boosts local economic growth, and improves community welfare.